The Analysis of Arabic Learning Error in Student of Madrasah Tsanawiyah - Saleh, Zeiburhanus; Murtadlo, Nurul; Rosyidi, Abdul Wahab; Hidayah, Eni Zulfa (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines grammatical (nahwu) and morphological (shorrof) errors in Arabic essays by secondary students, aiming to identify and categorize these errors and their causes. It also proposes pedagogical interventions to improve Arabic language instruction by enhancing both theoretical understanding and practical application of linguistic rules. Using a qualitative approach, data were collected through interviews with supervisors, teachers, and students, as well as classroom observations and document analysis of student essays. The analysis followed the Ellis-Huberman framework: data collection, reduction, presentation, and conclusion. Results revealed that student errors stemmed from limited understanding of grammar, interference from their mother tongue, and insufficient practice. Teacher-related factors included inadequate feedback and insufficient opportunities for practice. These issues hindered students' mastery of Arabic. The study recommends a combination of theoretical and applied exercises. Theoretical exercises help students grasp linguistic rules, while applied exercises improve writing skills. More frequent feedback and diverse teaching methods are also suggested to enhance learning outcomes. This research introduces a dual approach, integrating theoretical and applied exercises, offering valuable insights for improving Arabic language education at the secondary level.